Implementación piloto de un Proyecto Pedagógico Productivo en básica secundaria a través de la piscicultura: El caso de las disoluciones (2020)
The teaching of chemistry in high school has been carried out from a decontextualized perspective and focused on the contents and the teacher, a situation that limits the opportunity for students to engage in the construction of chemistry products and processes. In order to overcome these restrictions, this study set out to implement a PPP represented in fish farming in order to assist students in rural secondary cycle II, in the understanding of the topic of dissolutions together with the development of some skills for the lifetime. The methodology was qualitative and interpretive by case studies. This was configured by two phases: planning and implementation of a sequence of learning activities, and documentation of the reasoning and actions of the students and the teacher. The data from the different documentary sources were analyzed from the grounded theory, emerging a series of naturalistic generalizations supported by the affirmation that the PPP of rainbow trout breeding is a contextualized teaching orientation, which helped students build only the understanding of the phenomenon of dissolutions, but also the development of skills such as learning to learn and cooperative work with the aim of informing the cultivation of this kind of fish. Keywords: Contextualized teaching; Productive Pedagogical Project; Rural school; Fish farming, Chemistry education.